Validity and reliability of Traditional Chinese Medicine Constitution (TCMC) In Indonesian language - Intansari Nurjannah; Willie Japaries; Tjhia Khie Khiong (Berita Kedokteran Masyarakat, 2021)
AbstractObjectives: There are several methods to measure the condition of human health. In the field of complementary medicine, and which has the oldest history is Traditional Chinese medicine. One of the instruments to measure the level of a person's health condition is by using the Traditional Chinese Medicine Constitution (TCMC) in the form of questions with Likert scale and this instrument is divided into 9 dimensions. There are no publications regarding the validity and reliability of this tool in Indonesian. This study is to assess the construct validity and reliability of the TCMC in Indonesian.Method: TCMC  Indonesian’s translation was checked by Indonesian’s expert of traditional Chinese medicine, then it was tested on 50 people to find out whether the items in the questionnaire were understood or not. In the next step, TCMC was used for data collection in community service activities and as many as 391 TCMC filling data collected. After checking the completeness of the data, there were 377 data for analysis. Pearson correlation was used for measuring construct validity. Reliability analysis of this instrument was performed using Cronbach's alpha.Results: Complaints experienced by 377 respondents can be divided into several groups, namely headache (77), pain in extremities (75), digestive system (65), respiratory system (29), back pain (28), circulation system (13), hip pain (15), neck pain (12), problem in face (11), fever (7), eye problem (8), urinary system (8), toothache (5) and other complaints (24). All items from TCMC were valid with Sig value. (2-tailed) < 0.05. As for reliability, the value of Cronbach Alpha on Qi-Deficiency was 0.608 (moderate); Yang-deficiency was 0.728 (high); Yin-deficiency was 0.769 (high); Phleghm-dampness was 0.672 (moderate); Damp-heat was 0,501 (moderate); Blood Stasis was 0.531 (moderate); Qi-stagnation was 0.777 (high); Inherited special was 0.719 (high) and Balanced was 0.727 (high).Conclusions: TCMC in Indonesian is valid and reliable and can be used to measure human health from the perspective of Traditional Chinese Medicine. Key words: Validity, Reliability, Traditional Chinese Medicine Constitution